2017
DOI: 10.1002/glia.23277
|View full text |Cite
|
Sign up to set email alerts
|

Generation of a microglial developmental index in mice and in humans reveals a sex difference in maturation and immune reactivity

Abstract: The above referenced article was published with an incorrect image and legend for

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
65
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(70 citation statements)
references
References 34 publications
3
65
2
Order By: Relevance
“…A similar sex-biased depletion efficacy upon PLX3397 treatment in the murine cortex has recently been reported to be independent of pharmacokinetic concentrations of the drug in the brain [ 15 ]. This is in line with various studies reporting remarkable sex differences in microglia regarding key cellular functions as well as transcriptome and proteome profiles in health and disease [ 14 , 29 , 31 , 45 , 55 , 64 , 69 71 ]. These findings are getting more attention recently because of the well-documented sex-related susceptibility to psychiatric and neurological diseases, in which neuroinflammation is a common denominator [ 39 , 40 , 59 ].…”
Section: Discussionsupporting
confidence: 91%
“…A similar sex-biased depletion efficacy upon PLX3397 treatment in the murine cortex has recently been reported to be independent of pharmacokinetic concentrations of the drug in the brain [ 15 ]. This is in line with various studies reporting remarkable sex differences in microglia regarding key cellular functions as well as transcriptome and proteome profiles in health and disease [ 14 , 29 , 31 , 45 , 55 , 64 , 69 71 ]. These findings are getting more attention recently because of the well-documented sex-related susceptibility to psychiatric and neurological diseases, in which neuroinflammation is a common denominator [ 39 , 40 , 59 ].…”
Section: Discussionsupporting
confidence: 91%
“…6c right bottom; Supplementary Data 3) and found to be enriched for epithelial–mesenchymal transition (hypergeometric test, FDR < 0.05; Supplementary Table 6). Though the overlap of the microglia SDEGs with previous male and female microglia comparisons 33,41 was not significant, the overall result that female microglia are in a more immune-activated state was the same. Therefore, we conclude that the transcriptional differences between sexes appear in macrophages from the three tissues tested but that the specific differentially expressed genes are mostly tissue dependent.…”
Section: Resultscontrasting
confidence: 50%
“…Several previous studies have demonstrated sexual dimorphism in innate immunity mainly at the phenotypic level 59 . However, to the best of our knowledge, at the transcriptomic level of immune cells, only male and female microglia have been compared, showing that female microglia are in a more immune-activated state 33,41 . The numbers of male–female differentially expressed genes found in splenic MF and microglia were even higher than those in PC-MFs, but the identity of those genes was mostly tissue specific.…”
Section: Discussionmentioning
confidence: 99%
“…Sex-dependent differences in gene expression pattern become noticeable as early as embryonic phase two, although they are not fully displayed morphologically at this time [48,49]. A recently introduced microglia-specific developmental index, based on global gene expression patterns, showed accelerated microglial development in female compared to male mouse brains [50]. In utero, environmental factors can affect microglia development in a sex-dependent manner, and for example, germ-free conditions of the mother were recently shown to impair microglia maturation to a higher extent in male compared to female fetuses [48].…”
Section: Effects Of Sex On Glial Cell Developmentmentioning
confidence: 99%